2020
DOI: 10.3390/ijms21186622
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Roles of Androgen Receptor and Tip60 in Androgen-Dependent Prostate Cancer

Abstract: Androgen receptor (AR)-mediated signaling is essential for the growth and differentiation of the normal prostate and is the primary target for androgen deprivation therapy in prostate cancer. Tat interactive protein 60 kDa (Tip60) is a histone acetyltransferase that is critical for AR activation. It is well known that cancer cells rewire their metabolic pathways in order to sustain aberrant proliferation. Growing evidence demonstrates that the AR and Tip60 modulate key metabolic processes to promote the surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 89 publications
(186 reference statements)
0
7
0
Order By: Relevance
“…Additionally, the direct roles of androgen on NRF1-mediated transcription, AR-PGC-1α/PGC-1β-mediated transcription on oxidative phosphorylation-related members, and the global metabolic regulation of AR via CAMKK2-AMPK signaling or mTOR signaling have also been proposed to have roles in oxidative phosphorylation. 69,70 In summary, sex bias in immunity and energy metabolism were important features in shaping the adaptive and innate immunity in severe or critical COVID-19 patients, which usually displayed cell-typedependent and age-related characteristics between both genders. In advanced age, the sex bias was extremely prominent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the direct roles of androgen on NRF1-mediated transcription, AR-PGC-1α/PGC-1β-mediated transcription on oxidative phosphorylation-related members, and the global metabolic regulation of AR via CAMKK2-AMPK signaling or mTOR signaling have also been proposed to have roles in oxidative phosphorylation. 69,70 In summary, sex bias in immunity and energy metabolism were important features in shaping the adaptive and innate immunity in severe or critical COVID-19 patients, which usually displayed cell-typedependent and age-related characteristics between both genders. In advanced age, the sex bias was extremely prominent.…”
Section: Discussionmentioning
confidence: 97%
“…All three key features of the impact of AR inhibition or androgen deprivation on ETC are similar to the effects of stimulus by LPS and interferon on macro, which may account for the similar immune activation coordinated via the HIF1A‐IL1B axis. Additionally, the direct roles of androgen on NRF1‐mediated transcription, AR‐PGC‐1α/PGC‐1β‐mediated transcription on oxidative phosphorylation‐related members, and the global metabolic regulation of AR via CAMKK2‐AMPK signaling or mTOR signaling have also been proposed to have roles in oxidative phosphorylation 69,70 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that AR activation and expression promote the occurrence and development of tumors in the advanced stage and promote malignant behaviors, such as invasion, spread and proliferation, and tumor drug resistance through different mechanisms, such as inhibiting the secretion of relevant immune factors to promote tumor immune escape, inducing angiogenesis, and activating EMT [36][37][38][39][40][41][42] . AR is expressed in both physiological tissues and pathological tissues and plays important roles in various physiological activities of different tissues [43] and in the development of selective androgen receptor modulators (SARMs), which also take advantage of this mechanism [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Tip60 is another HAT that is closely associated with tumorigenesis [ 104 , 105 , 106 ] and may be involved in the regulation of DNA repair and the transcriptional activation of p53 and Myc [ 62 , 107 ]. Decreased expression of Tip60 results in low p53 acetylation levels and incomplete apoptosis signaling, which indicates transformation to a malignant tumor [ 108 ].…”
Section: Acetylationmentioning
confidence: 99%